Proximity Ligation Assay (PLA). (20th September 2018) - Alam, Muhammad S.
Abstract: Proximity ligation assay (PLA), also referred to as Duolink® PLA technology, permits detection of protein‐protein interactions in situ (at distances <40 nm) at endogenous protein levels. It exploits specific antibodies identifying (either directly or indirectly) the two proteins of interest and utilizes specific DNA primers covalently linked to the antibodies. A hybridization step followed by DNA amplification with fluorescent probes permit visualization of spots of proximity by fluorescence microscopy. Since the development of PLA in 2002, it has been increasingly used to detect the interaction between two proteins with high sensitivity and specificity. It is a simple and sensitive technique to study protein‐protein interaction in cells. © 2018 by John Wiley & Sons, Inc.